Motor function improvement and acceptability of non-invasive brain stimulation in patients with Parkinson's disease: a Bayesian network analysis - Qiu, Youjia; Yin, Ziqian; Wang, Menghan; Duan, Aojie; Xie, Minjia; Wu, Jiang; Wang, Zhong; Chen, Gang (Frontiers in Neuroscience, 2023)
Background Parkinson's disease (PD) is a neurodegenerative disorder defined by progressive motor and non-motor symptoms. Currently, the pro-cognitive effects of transcranial direct current stimulation (tDCS) and repetitive transcranial magnetic stimulation (rTMS) are well-supported in previous literatures. However, controversy surrounding the optimal therapeutic target for motor symptom improvement remains. Objective This network meta-analysis (NMA) was conducted to comprehensively evaluate the optimal strategy to use rTMS and tDCS to improve motor symptoms in PD. Methods We searched PubMed, Embase, and Cochrane electronic databases for eligible randomized controlled studies (RCTs). The primary outcome was the changes of Unified Parkinson's Disease Rating Scale (UPDRS) part III score, the secondary outcomes were Time Up and Go Test (TUGT) time, and Freezing of Gait Questionnaire (FOGQ) score. The safety outcome was indicated by device-related adverse events (AEs). Result We enrolled 28 studies that investigated various strategies, including high-frequency rTMS (HFrTMS), low-frequency rTMS (LFrTMS), anodal tDCS (AtDCS), AtDCS_ cathode tDCS (CtDCS), HFrTMS_LFrTMS, and Sham control groups. Both HFrTMS (short-term: mean difference (MD) −5.21, 95% credible interval (CrI) −9.26 to −1.23, long-term: MD −4.74, 95% CrI −6.45 to −3.05), and LFrTMS (long-term: MD −4.83, 95% CrI −6.42 to −3.26) were effective in improving UPDRS-III score compared with Sham stimulation. For TUGT time, HFrTMS (short-term: MD −2.04, 95% CrI −3.26 to −0.8, long-term: MD −2.66, 95% CrI −3.55 to −1.77), and AtDCS (short-term: MD −0.8, 95% CrI −1.26 to −0.34, long-term: MD −0.69, 95% CrI −1.31 to −0.08) produced a significant difference compared to Sham stimulation. However, no statistical difference was found in FOGQ score among the various groups. According to the surface under curve ranking area, HFrTMS ranked first in short-term UPDRS-III score (0.77), short-term (0.82), and long-term (0.84) TUGT time, and short-term FOGQ score (0.73). With respect to the safety outcomes, all strategies indicated few and self-limiting AEs. Conclusion HFrTMS may be the optimal non-invasive brain stimulation (NIBS) intervention to improve motor function in patients with PD while NIBS has generally been well tolerated. However, further studies focusing on the clinical outcomes resulting from the different combined schedules of tDCS and rTMS are required. Systematic review registration https://inplasy.com/inplasy-2023-4-0087/, identifier: 202340087.